Perspectives of the UST NSTP Facilitators on Disability and Disaster Risk Reduction and Management: A Qualitative Case Study - Sagun-Ongtangco, Karen S (Archīum Ateneo, 2016)
With the growing global concern on disaster, disaster risk reduction and management (DRRM) has become part and parcel of the school curricula. In the Philippines, integration of the DRRM in the school curricula is done through the National Service Training Program (NSTP) but review of literature suggests that most DRRM efforts are not disability-inclusive. Hence, this study examines the perspectives of the University of Santo Tomas (UST) NSTP facilitators on disability, their experience in teaching DRRM and their insights in making the DRRM module disability-inclusive. Using a case study as a research design and focus groups as a means of gathering data, this research is able to generate important insights based on the perspectives of the participants. Findings reveal that making DRRM disability-inclusive remains a challenge and is further confounded by factors relating to student, curriculum, facilitator and community issues. However, hope remains for feasible and concrete ways in making the UST-NSTP DRRM module disability inclusive. This study contributes in enriching the literature on how the UST-NSTP program can truly imbibe disability inclusiveness in its mandate to integrate DRRM in the school curriculum.